Retrograde nailing, trabecular metal implant and use of bone marrow aspirate concentrate after failed ankle joint replacement. Issue 2 (February 2021) - Sundet, Mads; Johnsen, Elena; Eikvar, Kari Helene; Eriksen, Marianne Lund
Highlights: 31 ankle replacements were removed and a tibio-talo-calcaneal fusion was done. The fusions were done with a novel combination of methods, with a retrograde nail, tantalum spacer, autologous bone grafting and bone marrow aspiration and concentration, dispensed in an osteoconductive pad. There were 2 non-unions (6.5%) and 1 delayed union. We present favorable patient-reported outcomes. Abstract: Background: Ankle fusion after removal of alloplasty is known to be a procedure with a high potential for non-unions and poor function, especially tibio-talo-calcaneal fusion. We wanted to review our results after using a novel method for the procedure, combining retrograde nailing with a trabecular metal implant and bone marrow aspirate concentration applied in an ostoconductive pad in addition to autologous bone grafting. Materials and methods: Retrospective review of a patient series, with some prospectively registered data. 31 ankles in 30 patients were operated from January 2016 to February 2019. Results: There were two non-unions (6.5%), and one delayed union, none of these were reoperated. The mean postoperative Manchester-Oxford Foot and Ankle Questionnaire score (MOxFQ) was 33.6 points. 9 patients scored an average MOxFQ at 72.9 immediately before surgery, while at follow-up this had decreased to 36.2, an improvement of 36.7 points (95% CI 18.3–54.9). There were 1 minor infection and 5 possible nerve injuries. One patient had the leg amputated 1 year after the surgery due to a non-related necrotizing fasciitis. Conclusion: We present reasonably good short to medium term patient satisfaction and fusion rates with this novel combination of techniques.